Right k-Weakly Regular Γ-Semirings. (14th December 2014) - Jagatap, R. D.
Abstract : The concepts of a k -idempotent Γ -semiring, a right k -weakly regular Γ -semiring, and a right pure k -ideal of a Γ -semiring are introduced. Several characterizations of them are furnished.